2013
DOI: 10.1111/febs.12333
|View full text |Cite
|
Sign up to set email alerts
|

Multimeric and differential binding of CIN85/CD2AP with two atypical proline‐rich sequences from CD2 and Cbl‐b*

Abstract: The CD2AP (CD2-associated protein) and CIN85 (Cbl-interacting protein of 85 kDa) adaptor proteins each employ three Src homology 3 (SH3) domains to cluster protein partners and ensure efficient signal transduction and down-regulation of tyrosine kinase receptors. Using NMR, isothermal titration calorimetry and small-angle X-ray scattering methods, we have characterized several binding modes of the N-terminal SH3 domain (SH3A) of CD2AP and CIN85 with two natural atypical proline-rich regions in CD2 (cluster of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 37 publications
0
13
0
Order By: Relevance
“…Thus, deviations in the loops' positions found in SH3-A may prevent stable docking of the arginine. This is reminiscent of recent work showing how the structure of the n-Src loop of CIN85 SH3-A, but not of CD2AP SH3-A, is able to promote heterotrimer formation, that is, two SH3 domains clamping onto a single c-Cbl peptide, and thus giving rise to both class I and II ligand binding [43]. Other notable differences in coordinate positions include those of the C-terminal peptide region.…”
Section: Discussionmentioning
confidence: 73%
“…Thus, deviations in the loops' positions found in SH3-A may prevent stable docking of the arginine. This is reminiscent of recent work showing how the structure of the n-Src loop of CIN85 SH3-A, but not of CD2AP SH3-A, is able to promote heterotrimer formation, that is, two SH3 domains clamping onto a single c-Cbl peptide, and thus giving rise to both class I and II ligand binding [43]. Other notable differences in coordinate positions include those of the C-terminal peptide region.…”
Section: Discussionmentioning
confidence: 73%
“…Subsequently, solution data were inconsistent with heterotrimer formation; rather, CIN85 SH3-1 most likely supported either class I or II binding in independent heterodimers (59). Most recently, a detailed biophysical study of the solution state revealed important contrasts between CIN85 and CD2AP (60). CD2AP appeared only to form heterodimers with CD2 or CBL-b peptides.…”
Section: Discussionmentioning
confidence: 99%
“…P 1 (K/L) 2 PxPR 6 ), both of which have been proven to enable distinct partner peptides to bind in the reverse class I orientation under certain conditions (45). In addition, Arg in motif position Ϫ2, which could promote class I binding (58,60), is absent.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, titration of the peptide induced changes in chemical shifts of amino acids implicated in binding to other PRsignature motifs (Fig. 5B) (Ceregido et al, 2013), indicating that both ligands compete for the same binding site. Accordingly, SEPT9-and Cbl-derived peptides occupied the same binding surface on SH3A domain of CIN85 (Fig.…”
Section: Sept9 Regulates Cbl-dependent Ubiquitylation Of Egf Receptorsmentioning
confidence: 95%
“…Purified SH3A was dialyzed overnight into a buffer containing 50 mM cacodylate pH 7.4. A reference assignment of the resonances of the 1 H, 15 N-HSQC of the protein was kindly provided by others (Ceregido et al, 2013). Because the protein construct used here slightly differed from the one documented previously, we performed measurements to confirm the assignment of the protein resonances.…”
Section: Nmr Spectroscopymentioning
confidence: 99%